PENGARUH PEMBERIAN COKELAT HITAM TERHADAP PENURUNAN INTENSITAS DISMENORRHEA PRIMER PADA REMAJA PUTRI DI SMA NEGERI 3 MAKASSAR - Ikawati, Nurul; Syamsuryanita, Syamsuryanita (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Primary dysmenorrhea is a medical condition that occurs during menstruation that can interfere with activity and requires treatment which is characterized by pain or pain in the abdominal or pelvic area. One of the non-pharmacological therapies includes consuming foods that stimulate the release of endorphins and serotonin, namely giving dark chocolate. The purpose of this study was to determine the effect of giving dark chocolate on reducing the intensity of primary dysmenorrhea in young girls at SMA Negeri 3 Makassar. This study used a pre-experimental research design with a research design "One Group Pretest- Posttest Design. And using Paired T Test analysis, the total sample of 30 young women who experienced primary dysmenorrhea within 3 months with the sampling technique using purposive sampling technique. Collecting data using the interview method and observation sheet, Numeric Rating Scale (NRS). The results of the study using the paired t-test T test obtained the value of ? = 0.000 <? = 0.05. This shows that there is an effect of giving dark chocolate on the decrease in the intensity of primary dysmenorrhea in adolescent girls. And dark chocolate can also be used as an alternative choice to reduce pain in adolescent girls with primary dysmenorrhea on a non-pharmacological basis.